Visual strength grading of Argentinean Eucalyptus grandis : Strength, stiffness and density profiles and corresponding limits for the main grading parameters - Piter, Juan Carlos Jesús (2004)
The present paper reports the results of an investigation regarding the design of a method for visually grading sawn timber of Argentinean Eucalyptus grandis. An empirical research project with four samples of beams and one sample of boards subjected to bending, one sample of boards subjected to tension and one sample of specimens subjected to compression, was carried out. The results obtained with specimens in structural sizes show the influence of the more important strength and stiffness reducing growth characteristics and allow to analyse different strength, stiffness and density profiles in comparison with the international strength class system established in the European standard EN 338. The research also reveals particularities for this timber species as the high ratio of modulus of elasticity and strength to density, in comparison with other deciduous species, among others.